2021
DOI: 10.1186/s12887-021-02590-7
|View full text |Cite
|
Sign up to set email alerts
|

Giant congenital nodular melanoma in a newborn: a case report and literature review

Abstract: Background Malignant melanoma (MM) arises predominantly after adolescence and is uncommon in children. Congenital MM in newborns is even rarer with a dearth of published literature; as a consequence, there is no uniform standard for the pathogenesis and treatment for neonatal malignant melanoma. Herein we report a case of giant congenital nodular MM in a newborn, including its clinical, imaging, pathological and molecular pathological features. This case is the largest giant congenital primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Findings from our literature review and reported cases can be found in supplemental digital content (See Tables 2 and 3, Supplemental Digital Content 3, http://links.lww. com/MR/A369 and Supplemental Digital Content 4, http:// links.lww.com/MR/A370 which shows the literature review for patients diagnosed neonatally with malignant melanoma) [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from our literature review and reported cases can be found in supplemental digital content (See Tables 2 and 3, Supplemental Digital Content 3, http://links.lww. com/MR/A369 and Supplemental Digital Content 4, http:// links.lww.com/MR/A370 which shows the literature review for patients diagnosed neonatally with malignant melanoma) [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital and neonatal malignant melanoma is a subgroup of the pediatric population, and the reported number of cases is limited to 13 case reports. Findings from our literature review and reported cases can be found in supplemental digital content (See Tables 2 and 3, Supplemental Digital Content 3, http://links.lww.com/MR/A369 and Supplemental Digital Content 4, http://links.lww.com/MR/A370 which shows the literature review for patients diagnosed neonatally with malignant melanoma) [3–15].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital malignant melanoma is present at birth or in the rst year of life and is exceedingly rare, with only 29 cutaneous cases (Table . 1) reported in the English language medical literature since 1925 (24,35). It is a unique entity and the epidemiological features is di cult to determine due to the limited cases.…”
Section: Subtypes Of Congenital MMmentioning
confidence: 99%